Acoustic properties of highly attenuating isotropic media - Rautenberg, Jens; Henning, Bernd
In the 1950's many investigations have been made in measuring the Young's and the shear modus of isotropic materials with acoustic waves. Therefore both the longitudinal and transversal sound velocities have been determined with only one specimen, that had to be large in comparison to the wavelength (Brown, Reynolds, Dunegan). Therewith the method was suited only for low absorbing materials. In the 1990's further developments led to mono mode rods to describe viscoelastic properties. Their diameters had to be very small for high frequencies, thus giving practical values up to 65 kHz (Benatar). This contribution is about a tubular multi mode specimen and its application for the simultaneous measurement of the abovementioned acoustic properties at high frequencies.